2023
DOI: 10.2147/dmso.s400285
|View full text |Cite
|
Sign up to set email alerts
|

Association of Bone Turnover Markers with Type 2 Diabetes Mellitus and Microvascular Complications: A Matched Case-Control Study

Abstract: The aim of this study was to evaluate the association of bone turnover markers (BTMs) with type 2 diabetes mellitus (T2DM) and microvascular complications. Methods: A total of 166 T2DM patients and 166 non-diabetic controls matched by gender and age were enrolled. T2DM patients were subclassified into groups based on whether they had diabetic peripheral neuropathy (DPN), diabetic retinopathy (DR), and diabetic kidney disease (DKD). Clinical data including demographic characteristics and blood test results [ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Many studies suggest that due to chronic hyperglycemia, the formation of ROS may be associated with collagen glycation, which is an important factor [4,5]. Overall, bone damage in T2DM can be caused by multiple mechanisms: accumulation of advanced glycation end products (AGEs) [79], increased levels of pro-inflammatory cytokines (e.g., IL-6, TNF-α) [80], sclerostin [81], leptin [80], lower levels of OC [11,82]), procollagen I N-terminal propeptide (P1NP) [83,84], parathyroid hormone (PTH) [85], and impairment of osteoblastogenesis [86]. The status of low bone turnover in T2DM is also reflected in lower levels of bone resorption markers (e.g., TRAP5b and C-telopeptide of type I collagen (CTx)) [82,85].…”
Section: Biologically Active Molecules Responsible For Impaired Bone ...mentioning
confidence: 99%
“…Many studies suggest that due to chronic hyperglycemia, the formation of ROS may be associated with collagen glycation, which is an important factor [4,5]. Overall, bone damage in T2DM can be caused by multiple mechanisms: accumulation of advanced glycation end products (AGEs) [79], increased levels of pro-inflammatory cytokines (e.g., IL-6, TNF-α) [80], sclerostin [81], leptin [80], lower levels of OC [11,82]), procollagen I N-terminal propeptide (P1NP) [83,84], parathyroid hormone (PTH) [85], and impairment of osteoblastogenesis [86]. The status of low bone turnover in T2DM is also reflected in lower levels of bone resorption markers (e.g., TRAP5b and C-telopeptide of type I collagen (CTx)) [82,85].…”
Section: Biologically Active Molecules Responsible For Impaired Bone ...mentioning
confidence: 99%
“…Furthermore, Jain et al.,studies confirmed that visceral adipose tissue (VAT) is negatively associated with bone mineral density ( 23 ). On the other hand, in T2D BMD is normal or above normal,likely protective against vertebral fractures ( 24 ), but some studies show reduced BMD ( 25 , 26 ) due to accumulation of advanced glycation end products (AGEs) ( 27 , 28 ) increased proinflammatory cytokines such as TNF-a, IL-6 ( 28 , 29 ) high sclerostin levels ( 30 ) leading to reduction in bone formation, OCN ( 31 ) and (Procollagen I N-terminal propeptide) P1NP levels in T2DM ( 31 , 32 ) and impairment in osteoblastogenesis ( 33 35 ). There is also reduction in bone resorption markers (CTX and TRAP5b) ( 28 ) though bone turnover markers are not as predictive of fractures compared to BMD and maybe difficult to interpret,.…”
Section: Introductionmentioning
confidence: 99%